2021
DOI: 10.1016/j.redox.2021.101900
|View full text |Cite
|
Sign up to set email alerts
|

Are trace element concentrations suitable biomarkers for the diagnosis of cancer?

Abstract: Despite advances in cancer research, cancer is still one of the leading causes of death worldwide. An early diagnosis substantially increases the survival rate and treatment success. Thus, it is important to establish biomarkers which could reliably identify cancer patients. As cancer is associated with changes in the systemic trace element status and distribution, serum concentrations of selenium, iron, copper, and zinc could contribute to an early diagnosis. To test this hypothesis, case control studies meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 69 publications
0
25
0
2
Order By: Relevance
“…Since copper plays an important role in the cellular function and metabolism, the question arises as to whether there are significant differences in Cu levels in cancer patients in comparison with healthy cohorts, and if yes, whether Cu levels can be used as a reliable biomarker of disease progression and response to treatment [ 15 ]. Cu concentrations were determined from emission spectrograms or by flame atomic absorption spectrometry in whole blood, plasma [ 16 ] or serum [ 15 ], toenail [ 17 ], hair [ 18 ], saliva [ 19 ], and tissues [ 20 ]. Many studies reported a positive correlation between circulating Cu levels and cancer progression, in particular breast cancer.…”
Section: Systemic Changes In Cu Homeostasis Of Cancer Patientsmentioning
confidence: 99%
“…Since copper plays an important role in the cellular function and metabolism, the question arises as to whether there are significant differences in Cu levels in cancer patients in comparison with healthy cohorts, and if yes, whether Cu levels can be used as a reliable biomarker of disease progression and response to treatment [ 15 ]. Cu concentrations were determined from emission spectrograms or by flame atomic absorption spectrometry in whole blood, plasma [ 16 ] or serum [ 15 ], toenail [ 17 ], hair [ 18 ], saliva [ 19 ], and tissues [ 20 ]. Many studies reported a positive correlation between circulating Cu levels and cancer progression, in particular breast cancer.…”
Section: Systemic Changes In Cu Homeostasis Of Cancer Patientsmentioning
confidence: 99%
“…6 These results suggest that the Se present in Plasmax protects cells from impairment by lipid peroxidation and ferroptosis. The concentration of Se in tumor tissue is almost fourfold higher compared to that in normal cells, 22,23 in particular, drug-resistant cancer cells, suggesting that cancer cells utilize selenoenzymes to protect themselves from ROS-producing anticancer agents. 1,24 Although the scientific community has known about ferroptosis, a type of programmed cell death, for quite a long time, Stockwell's group coined the term ferroptosis and described its key features.…”
Section: Seleniummentioning
confidence: 99%
“…However, treatment of cancerous prostate tumors by elevating dietary or serum Zn 2+ , which does not directly affect the “free” Zn 2+ content of prostate cells, proved controversial, and more specific tools were sought [ 98 , 99 ]. In breast cancer patients, measurement of total Zn 2+ in the serum or within the malignant cells demonstrated abnormal concentrations, suggesting the involvement of Zn 2+ dysregulation in progression of this malignancy as well [ 100 , 101 ]. While serum Zn 2+ levels are reduced in most cancers, breast and lung tumor tissues have elevated levels of “free” Zn 2+ when compared to the normal tissue [ 102 , 103 ].…”
Section: Zn 2+ Homeostasis and Zn 2+ Transporters In Breast Cancermentioning
confidence: 99%